Hohenbergia ituberaensis (Bromeliaceae): a new white-flowered species from Bahia, Brazil - Cavalcante, Brayan Paiva; de Souza, Everton Hilo; Versieux, Leonardo M.; Martinelli, Adriana Pinheiro (Phytotaxa, 2020)
We describe a new species of Hohenbergia (Bromeliaceae) from Brazil, H. ituberaensis, a rare species, so far only known from Ituberá municipality, Bahia State, in an area of the Atlantic Forest. The species is similar to H. stellata, presenting a pinkish inflorescence, congested and non-divided branches, pinkish and large floral bracts hiding the sepals, spatulate petals with a slightly reflexed apex. However, it differs by the white petals, as a diagnostic characteristic. The type specimen was collected in a small forest fragment and here this species is categorized as Vulnerable. Additionally, we compared this new species to Hohenbergia belemii and H. capitata, which are also similar to H. stellata, due to the red/pinkish characteristics of the branches, with large flowers and well-developed floral bracts. An illustration, an occurrence map, taxonomic comments and a table comparing the main characters of these four species are provided.